Human Tau Aggregates Are Permissive to Protein Synthesis-Dependent Memory in Drosophila Tauopathy Models. - Vourkou, E.; Rouiz Ortega, E.D.; Mahajan, S.; Mudher, A.; Skoulakis, E.M.C. (Journal of Neuroscience, 2023)
Tauopathies including Alzheimer's disease, are characterized by progressive cognitive decline, neurodegeneration, and intraneuronal aggregates comprised largely of the axonal protein Tau. It has been unclear whether cognitive deficits are a consequence of aggregate accumulation thought to compromise neuronal health and eventually lead to neurodegeneration. We use the Drosophila tauopathy model and mixed-sex populations to reveal an adult onset pan-neuronal Tau accumulation-dependent decline in learning efficacy and a specific defect in protein synthesis-dependent memory (PSD-M), but not in its protein synthesis-independent variant. We demonstrate that these neuroplasticity defects are reversible on suppression of new transgenic human Tau expression and surprisingly correlate with an increase in Tau aggregates. Inhibition of aggregate formation via acute oral administration of methylene blue results in re-emergence of deficient memory in animals with suppressed human Tau (hTau)[0N4R] expression. Significantly, aggregate inhibition results in PSD-M deficits in hTau[0N3R]-expressing animals, which present elevated aggregates and normal memory if untreated with methylene blue. Moreover, methylene blue-dependent hTau[0N4R] aggregate suppression within adult mushroom body neurons also resulted in emergence of memory deficits. Therefore, deficient PSD-M on human Tau expression in the Drosophila CNS is not a consequence of toxicity and neuronal loss because it is reversible. Furthermore, PSD-M deficits do not result from aggregate accumulation, which appears permissive, if not protective of processes underlying this memory variant.SIGNIFICANCE STATEMENT Intraneuronal Tau aggregate accumulation has been proposed to underlie the cognitive decline and eventual neurotoxicity that characterizes the neurodegenerative dementias known as tauopathies. However, we show in three experimental settings that Tau aggregates in the Drosophila CNS do not impair but rather appear to facilitate processes underlying protein synthesis-dependent memory within affected neurons.